(untitled) (Archives of Pediatrics of Uruguay, 2025)
Vascular lesions comprise a group of entities that are sometimes confused in terms of definitions and terms. It is common that health staff does not use the same nomenclature to refer to these injuries, which might lead to errors or misinterpretation. The present paper intends to harmonize concepts based on the existing classification of vascular lesions provided by the International Society for the Study of Vascular Anomalies (ISSVA). This Society split them into two large groups: vascular tumors (abnormal cell proliferation) and vascular malformations (abnormalities in the architecture of the vascular endothelium). They describe the characteristics of infantile hemangioma, congenital hemangioma, kaposiform hemangioendothelioma and tufted angioma. They differ in their clinical, imagenaegenological, histological, prognostic and therapeutic characteristics. Treatment can be simple or complex and it must be adjusted to every patient, which is why they are approached by a multidisciplinary team ideally made up of a pediatric surgeon, vascular surgeon, interventional imaging specialist, dermatologist, plastic surgeon, among other specialists, who know the pathologies and have proper management of them.